2020
DOI: 10.3348/kjr.2019.0711
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dual-Energy Spectral Computed Tomography to Thoracic Oncology Imaging

Abstract: Computed tomography (CT) is an important imaging modality in evaluating thoracic malignancies. The clinical utility of dual-energy spectral computed tomography (DESCT) has recently been realized. DESCT allows for virtual monoenergetic or monochromatic imaging, virtual non-contrast or unenhanced imaging, iodine concentration measurement, and effective atomic number (Zeff map). The application of information gained using this technique in the field of thoracic oncology is important, and therefore many studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 49 publications
0
12
1
Order By: Relevance
“…We found the lung cancers accumulated more iodine than benign solid nodules, which was consistent with previous reports (15,(17)(18)(19). Zeff quantitatively represents the composite atom for a compound or mixture of various materials (32). Gonzaĺez-Peŕez et al found lower Zeff correlated with malignant pulmonary lesions, which was contrary to our result (38).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found the lung cancers accumulated more iodine than benign solid nodules, which was consistent with previous reports (15,(17)(18)(19). Zeff quantitatively represents the composite atom for a compound or mixture of various materials (32). Gonzaĺez-Peŕez et al found lower Zeff correlated with malignant pulmonary lesions, which was contrary to our result (38).…”
Section: Discussioncontrasting
confidence: 99%
“…In recent years, DECT is an emerging diagnostic technology with various clinical applications, especially in thoracic imaging (31)(32)(33). IC, the most commonly used quantitative parameter of DECT, is considered to be equivalent to the actual value of enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdullayev et al also made use of the identical SDCT scanner to successfully identify metastatic spine disease on contrast-enhanced VNCa images, which might serve as well as a practical proof of concept [12]. Several further authors consider this approach promising and warrant further investigation [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…By now, dual-energy CT (DECT) is a widely available technology, which holds the potential to narrow the diagnostic uncertainty of conventional CT concerning metastatic spine disease [12][13][14]. DECT exploits the physical phenomenon that the interaction of an X-ray beam with any absorbing material depends on a material-specific combination of the photoelectric effect and Compton scattering.…”
Section: Introductionmentioning
confidence: 99%